PENENTUAN HARGA JUAL GAS BUMI MENGGUNAKAN INPUT OUTPUT ANALYSIS - Jati A. Wibowo (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2019)
Natural Gas shortage and low relative purchasing power causes the happening of competition of exploiting of earth gas by national industry. The Government must do optimization of allocation of earth gas for industry in country by giving the biggest efficacy nationally. Input-output analysis is framework developed by Wassily Leotief by the end of 1930s. This research gets Nobel Ekonomi is 1973. This method has been applied widely in so many area. Analysis input-output applied to know multiplier effect an input to sector or certain industry which will be applied as reference in determining contribution nationally. The result of natural gas exploiting optimization applies analysis input-output besides getting multiplier effect, also gets relative gas selling price between sectors.